Renewable Energy Production in Primary Energy in Poland – Comparative Analysis of Selected European Union Countries - Malgorzata PIETA-KANURSKA (Communications of International Proceedings, 2021)
Electricity consumption and greenhouse gas production are considered the primary sources of increasing climate change. All European Union countries have committed themselves to increase the share of renewable energy in their final consumption. Poland has also taken strategic action to meet the challenge of increasing its energy production from renewable sources. This article aims to characterise the volume of primary energy production with particular emphasis on energy from renewable sources in Poland compared to selected EU countries, taking into account the population potential of the countries analysed (energy production per 1000 inhabitants). The analyses were conducted in international cross-sections of selected EU countries and, in the case of Poland, also concerning its 16 voivodeships. The article also takes into account the potential population changes and how Poland is perceived against other EU countries regarding the environmental impact of energy production.
Keywords: Renewable energy; primary energy; sustainable development; energy production per 1000 inhabitants; EU